Manual for the design of steelwork building structures. - Rathbone, A. J. (Institution of Structural Engineers, 2008)
This manual provides guidance on the design of single and multi-storey building structures using structural steelwork. Structures designed in accordance with this manual will normally comply with BS 5950-1: 2000 as amended to March 2008. --